Roles and Competencies of Librarians in Academic libraries - แสนวา, ศุมรรษตรา (Journal of Behavioral Science for Development, 2014)
บทบาทและความรู้ความสามารถของบรรณารักษ์ห้องสมุดสถาบันอุดมศึกษา Abstract This research aimed at examining factors leading to role and competency of academic librarians and to study their role and competency. This research divided into 2 stages. In the first stage, the examination of factors leading to role and competency of academic librarians was explored. And in the final stage, role and competency of academic librarians were conducted. In the first stage, the study sample included 197 librarians and administrators from 56 university libraries by simple random sampling. The tool employed for this stage was questionnaire. In the final stage, the study sample included 23 library and information science experts by purposive sampling. The tool employed for this stage were questionnaire and interview. The collected data were analyzed by frequency, percentage, means and standard deviation. The research findings revealed that there were 5 factors affecting the role and competency of academic librarians at high level: 1) information technology and innovation 2) library user 3) information source 4) library policy and 5) academic institution policy. For the role and competency of academic librarians, 100 % of experts agreed with 5 aspects of role and competency of academic librarians: 1) role of professional 2) role of learning and instruction promotion 3) professional competency 4) information technology competency and skill and 5) general competency. Keywords: performance appraisal, participation บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อศึกษาปัจจัยที่เกี่ยวข้องกับบทบาทและความรู้ความสามารถของบรรณารักษ์ห้องสมุดสถาบันอุดมศึกษา และศึกษาบทบาทและความรู้ความสามารถของบรรณารักษ์ห้องสมุดสถาบันอุดมศึกษา ดำเนินการวิจัยเป็น 2 ระยะ ได้แก่ การวิจัยระยะที่ 1 เป็นการศึกษาปัจจัยที่มีผลต่อบทบาทและความรู้ความสามารถของบรรณารักษ์ห้องสมุดสถาบันอุดมศึกษา เป็นผู้ปฏิบัติงานห้องสมุดจำนวน 197 คน จากสถาบันอุดมศึกษา 56 แห่ง ได้มาจากการสุ่มตัวอย่างด้วยแบบง่าย เก็บข้อมูลจากแบบสอบถาม และการวิจัยระยะที่ 2 ยืนยันบทบาทและความรู้ความสามารถของบรรณารักษ์ห้องสมุดสถาบันอุดมศึกษา จากผู้เชี่ยวชาญด้านบรรณารักษศาสตร์และสารสนเทศศาสตร์ จำนวน 23 คน เลือกด้วยวิธีเจาะจง เก็บรวบรวมข้อมูลด้วยแบบสอบถามและสัมภาษณ์ วิเคราะห์ข้อมูลโดยใช้ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย และค่าความเบี่ยงเบนมาตรฐาน ผลการวิจัยโดยรวมพบว่า ปัจจัยที่เกี่ยวข้องกับบทบาทและความรู้ความสามารถของบรรณารักษ์อยู่ในระดับมาก มี 5 ด้าน ได้แก่ ด้านเทคโนโลยีสารสนเทศและนวัตกรรม ด้านผู้ใช้บริการ ด้านทรัพยากรสารสนเทศ ด้านนโยบายของห้องสมุด และด้านนโยบายของสถาบันอุดมศึกษา ตามลำดับ ที่นี้การยืนยันจากผู้เชี่ยวชาญส่วนใหญ่ร้อยละ 100 เห็นด้วยกับบทบาทและความรู้ความสามารถ 5 ด้าน ได้แก่ บทบาทในหน้าที่หลักทางวิชาชีพ บทบาทในการสนับสนุนการเรียนการสอน ความรู้ความสามารถทางวิชาชีพ ความรู้และทักษะด้านเทคโนโลยีสารสนเทศ และความรู้ความสามารถทั่วไป